Trend analysis for daily gold price in Malaysia / Nurul Husna Jamian ... [et al.] - Jamian, Nurul Husna; Wan Abdul Aziz, Wan Noor Hayatie; Mohammad Hamzah, Mohd Hafiz; Azhar, Farah Waheeda (Universiti Teknologi MARA, Perak, 2023)
The awareness of gold price trends is essential for promoting financial stability, wealth preservation, diversified investments, preserving cultural practices and economic stability. However, there is a noticeable absence of studies utilizing least square models to analyze the daily gold price trend (RM), highlighting a gap in research on this crucial financial aspect. This study aims to uncover trends in daily gold prices over time, examine the correlation between gold prices and time, and develop a least squares model for analyzing daily gold price (RM). The dataset consists of 1569 daily gold price observations in Malaysia from August 2018 to November 2022, obtained through the secondary data collection method from the Public Gold website. The study discovered a positive correlation between Gold Price (RM) and Time (Day) with Pearson Correlation Coefficient of 0.879. This implies that, over the specified time frame, there is a consistent upward trend in gold prices, a critical insight for investors and financial decision-makers. Furthermore, the developed least squares model features an intercept of 182.801 and a slope of 0.074. This slope signifies that for each day's increase in time, the gold price is anticipated to rise by RM0.074. The daily gold price analysis not only provides valuable insights into gold price patterns but also offers a practical tool for making informed financial decisions and predicting future gold prices, thereby contributing to economic stability, and fostering responsible and sustainable gold practices.